Authority of the Regional Government in Processing Oil Palm Plantation Licensing in Kampar Regency - Intan Pratiwi, Maya; Andora, Hengki (Dinasti Research, 2024)
Opportunities for oil palm plantations and the oil palm processing industry are still in high demand, both to meet domestic and foreign markets. This condition is a promising business opportunity for the company. Even in times of economic crisis, it has proven to be able to survive and continue to grow. In this study, first, the authority of the local government in processing oil palm plantation licensing in Kampar Regency is in terms of issuing location permits, issuing plantation business permits and supervising plantation activities, but at the implementation stage there have been procedural violations in the field of oil palm plantation licensing in Kampar Regency, which indicators can be seen from the stages that have been exceeded or not implemented in the process of issuing oil palm plantation licenses. Second, the factors that hinder the granting of oil palm plantation permits in Kampar Regency are complex and changing requirements, licensing regulations that are often updated and the addition of new requirements make the licensing process longer and more complex, this is often a complaint from business actors, overlapping authorities, land conflicts, environmental considerations, pressure from the community, limited human resources, budget, and infrastructure in the local government can be hindering the effectiveness of the implementation of supervision and control over plantation activities. And corrupt practices in the licensing process are often suspected by the public, this can slow down or even stop the licensing process.